Human remains of Ovaherero and Nama: Transnational dynamics in post-genocidal restitutions - Elise Pape (Human Remains and Violence, 2018)
Taking its starting point from a socio-anthropological study combining biographical interviews, semi-structured interviews and ethnographic observations collected between 2016 and 2018 in Germany, France and the United States among Ovaherero and Nama activists, and also members of different institutions and associations, this article focuses on the question of human remains in the current struggle for recognition and reparation of the genocide of the Ovaherero and Nama from a transnational perspective. First, the text shows the ways in which the memory of human remains can be considered as a driving force in the struggle of the affected communities. Second, it outlines the main points of mismatches of perspective between descendants of the survivors and the responsible museums during past restitutions of human remains from German anthropological collections. Third, the article more closely examines the resources of Ovaherero in the United States in the struggle for recognition and reparation, the recent discovery of Namibian human remains in the American Museum of Natural History in New York City and the questions that it raises.